Konstruksi Gaya Komunikasi Gen Alpha dalam Hiperrealitas TikTok di SMP Negeri 01 Tegal - Dita Alena Sari; Didi Permadi; Inas Sany Muyassaroh (PERSPEKTIF, 2026)
The rapid growth of TikTok has transformed adolescents' communication practices by creating a hyperreal digital environment that shapes language use, self-expression, and identity construction. While previous studies have primarily examined TikTok's influence on social interaction and digital behavior, limited attention has been given to how hyperreality constructs the communication styles of Generation Alpha within school settings. This study aims to analyze the construction of Generation Alpha's communication style in the context of TikTok hyperreality at SMP Negeri 01 Tegal by integrating Baudrillard's theory of hyperreality with Norton's communication style framework. A qualitative phenomenological approach was employed through observations, in-depth interviews, and documentation involving 15 students who actively use TikTok. The findings reveal that TikTok functions not only as a social media platform but also as a symbolic environment that reconstructs students' communication practices. Five dominant communication styles—dramatic, animated, open, friendly, and impression-leaving—emerged as manifestations of continuous exposure to TikTok's digital culture. The study further demonstrates that hyperreality encourages students to adopt viral expressions, digital symbols, and idealized online identities, resulting in more expressive yet less formal communication patterns and diminishing the intensity of face-to-face interactions. These findings extend the application of hyperreality theory to the context of adolescent digital communication and provide practical implications for strengthening digital literacy and communication ethics programs within schools.